Gender Outcomes Harvesting in Climate Change, Agriculture and Food Security: A meta-analysis - Verzosa, Fatima; Gonsalves, Julian Francis; Barbon, Wilson John; Monville-Oro, Emilita (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
Within the context of the promotion and adoption of climate-smart agriculture (CSA) options or practices, this paper is a meta-analysis that focuses on gender outcomes resulting from women’s adaptation strategies, in response to constraints brought on by their normative and cultural environment, expectations emanating from their reproductive and productive roles, and gender disparities that contribute to gender inequality and women’s economic disempowerment.